Analisis Dan Perancangan Sistem Informasi Layanan Pengiriman Cargo Udara Berbasis Web Pada PT. Citilink Indonesia - Rasyad, Haza Ibnu; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2020)
PT. Citilink Indonesia is one of the companies engaged in low cost carrier services for passengers and air freight goods (air cargo). In the air freight forwarding service, it still uses semi manual, where customers who want to deliver goods must come directly to the company to provide details of the goods to be sent. To overcome this problem, the need for an information system service for air cargo delivery based on the website to facilitate the process of shipping goods and track the delivery of goods. In designing this attendance system using website-based programming using the PHP programming language and processing MySQL databases.